Reserves of resource saving in the manufacture of brake drums of cargo vehicles - Lysenkov, Vitalii; Demin, Dmitriy (Scientific Route OÜ, 2022)
The object of this research: cast iron grade DSTU EN 1561 (EN-GJL-200), used for the manufacture of brake drums for KrAZ trucks. Investigated problem: obtaining the effect of resource saving by minimizing the consumption of alloying elements, while maintaining a given level of mechanical properties of cast iron. The main scientific results: experimental and theoretical confirmation of the possibility of reducing the content of Cr introduced into the alloy to increase its strength, as part of the Cr:Ni alloying complex, was obtained. It is shown that a decrease in the Cr content from the upper range (0.34–0.48) % to the lower one (0.21–0.33) % does not affect the ultimate strength of cast iron (σb). The obtained values of σb for both ranges are statistically equal: σb=234 MPa, Sσb=16.22 MPa for the upper range of Cr content and σb=240 MPa, Sσb=19.86 MPa for the lower range of Cr content, where Sσb is the standard deviation of the tensile strength value. It is established that the hardness (HB) is also unchanged: the obtained values of HB for both ranges are statistically equal: HB213, SHB=9.1 for the upper range of Cr content and HB212, SHB=12 for the lower range of Cr content, where SNB is the standard deviation of hardness. At the same time, it has been statistically proven that the Cr:Ni ratio can be shifted towards lower Cr values – from Cr:Ni=2.2:1 in the existing technology to Cr:Ni=1.76:1 in the ones proposed in this study. The area of practical use of the results of the study: the results obtained can be used in machine-building enterprises specializing in the manufacture of hull cast iron parts with a foundry cycle. The adaptation of the proposed results to the actual conditions of the foundry production of implementing organizations will be minimal if they comply with the following criteria: cast iron grade, predominant or minimum casting wall thickness, temperature regime of melting and out-of-furnace treatment, ferroalloys and modifiers used. Innovative technological product: iron smelting technology for commercial vehicle brake drum castings that reduces production costs while maintaining a given level of mechanical properties. The scope of the technological innovative product: technological regimes for producing cast iron for the production of cast brake drums for trucks.
Keywords: truck brake drum; cast iron with lamellar graphite; mechanical properties of cast iron; alloying; modification